T and B cell clonal expansion in Ras‐associated lymphoproliferative disease (RALD) as revealed by next‐generation sequencing. (5th June 2017) - Levy‐Mendelovich, S.; Lev, A.; Rechavi, E.; Barel, O.; Golan, H.; Bielorai, B.; Neumann, Y.; Simon, A. J.; Somech, R.
Summary: Ras‐associated lymphoproliferative disease (RALD) is an autoimmune lymphoproliferative syndrome (ALPS)‐like disease caused by mutations in Kirsten rat sarcoma viral oncogene homologue ( KRAS ) or neuroblastoma RAS viral (V‐Ras) oncogene homologue ( NRAS ). The immunological phenotype and pathogenesis of RALD have yet to be studied extensively. Here we report a thorough immunological investigation of a RALD patient with a somatic KRAS mutation. Patient lymphocytes were analysed for phenotype, immunoglobulin levels and T cell proliferation capacity. T and B cell receptor excision circles (TREC and KREC, respectively), markers of naive T and B cell production, were measured serially for 3 years. T and B cell receptor repertoires were studied using both traditional assays as well as next‐generation sequencing (NGS). TREC and KREC declined dramatically with time, as did T cell receptor diversity. NGS analysis demonstrated T and B clonal expansions and marked restriction of T and B cell receptor repertoires compared to healthy controls. Our results demonstrate, at least for our reported RALD patient, how peripheral T and B clonal expansions reciprocally limit lymphocyte production and restrict the lymphocyte receptor repertoire in this disease. Decreased naive lymphocyte production correlated with a clinical deterioration in our patient's immune status, suggesting that TREC and KREC may be used as an aid in monitoring disease progression. Both the methodologies used here and the conclusions regarding immune homeostasis may be applicable to the research of ALPS and other immune dysregulation syndromes. Abstract : We thoroughly investigated a patient with Ras associated lymphoproliferative disease (RALD) harboring a somatic KRAS mutation. T and B cell production dramatically declined with time and next generation sequencing analysis demonstrated severely abnormal cell receptor diversity. Our results show how peripheral T and B clonal expansions reciprocally limit lymphocyte production and restrict the lymphocyte receptor repertoire in this disease, ending in abnormal immune homeostasis.